Application of the Geocar in the learning of convexos polígonos in the students of the fourth grade - Meza-Paucar, Toño (2019)
Various changes taking Peruvian education poses challenges in finding alternative solutions to improve the quality of education of our students in the area of mathematics, which is why we introduced Geocar educational material through a project called "Implementation of Geocar in convex polygons learning in secondary education students "whose objective was to design the material, applying learning in convex polygons and then analyze and evaluate its application Geocar in the fourth grade students of secondary IEA La Primavera. Also, in order to deepen the analysis and interpretation of the results, we would like to test the following hypothesis: The application of geocar improves learning of convex polygons, and for this purpose the research design was quasi-experimental with the application a pre-test and post-test, using simple random probability sampling was chosen two working groups comprised of students from fourth grade "a" and "B" high school enrolled in the academic year 2012. In the first group developed significant learning process using Geocar material, while the second group used the conventional approach. We conducted field work to get the results, and processing for analysis and interpretation. Coming to the conclusion that the application of geocar positively influences learning of convex polygons in IE students The Spring of the province of Leoncio Prado, creating meaningful learning them in the dimensions of reasoning and proof, communication, math and problem solving.